Attribution: A Morphological and Phonetic Study - Al Masa’eed , Nadwa Ali (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aimed to explore the changes that occur to the structure of the word when it gets attributed, especially the defective one. The study also analyzes those changes in light of modern phonology. Methods: This study used the descriptive analytical approach. This approach conveniently correlated with the ancient linguists’ treatment of the subject and their explanations in an endeavor to show their methodology. This approach also helped the researcher present modernist linguists and syntacticians’ views to show their agreement or diversion from their ancient linguists and syntacticians. Results: The study results showed that the phonemic factor is the underlying cause of changes in the structure of the word when attributed. These changes are necessitated to serve different functionalities: to construct a normal syllable, modify less prevalent syllable or to get rid of succession. These phonemic changes may take effect using shortening or omission. Conclusion The study recommended that the phonetic explanation incarnated in the adequacy of the syllable structure constitutes the main reason for which a word structure is changed in the case of attribution. The study also avers that both ancient and modernist syntacticians equivocally pinpointed the importance of phonetic explanation in the formation of the word structure.